CRISPR/Cas9 for the treatment of haematological diseases: a journey from bacteria to the bedside. (7th June 2020) - Humbert, Olivier; Samuelson, Clare; Kiem, Hans‐Peter
Summary: Genome editing therapies represent a significant advancement in next‐generation, precision medicine for the management of haematological diseases, and CRISPR/Cas9 has to date been the most successful implementation platform. From discovery in bacteria and archaea over three decades ago, through intensive basic research and pre‐clinical development phases involving the modification of therapeutically relevant cell types, CRISPR/Cas9 genome editing is now being investigated in ongoing clinic trials. Despite the widespread enthusiasm brought by this new technology, significant challenges remain before genome editing can be routinely recommended and implemented in the clinic. These include risks of genotoxicity resulting from off‐target DNA cleavage or chromosomal rearrangement, and suboptimal efficacy of homology‐directed repair editing strategies, which thus limit therapeutic options. Practical hurdles such as high costs and inaccessibility to patients outside specialised centres must also be addressed. Future improvements in this rapidly developing field should circumvent current limitations with novel editing platforms and with the simplification of clinical protocols using in vivo delivery of editing reagents.